IMPLEMENTASI MODEL DAN SISTEM PENDIDIKAN PESANTREN PERSATUAN ISLAM - Asep Abdul Aziz; Nurti Budiyanti; Andewi Suhartini; Nurwadjah Ahmad (stit-islamic-village, 2021)
The pesantren learning system is considered as an alternative system that is presented in overcoming the various moral problems that occur today. Pesantren Persatuan Islam 1-2 Bandung, as the first pesantren to give birth to other pesantren regulations, certainly has a unique model and education system. This study used a qualitative approach with a case study method in Islamic Boarding School 1-2 Bandung. The results illustrate that the education model of the Islamic Boarding School 1-2 Bandung has three educational paths, namely the Islamic boarding school education pathway, the school education pathway, and the out-of-school education pathway. The pesantren education pathway and the school education pathway are presented in the general curriculum and pesantren curriculum, both boarding and non-boarding, which are regulated at each level of education at the Islamic Boarding School 1-2 Bandung, namely the Tajhiziyyah, Tsanawiyyah, Diniyyah Wustha, and Mualimien levels. The learning system presented seeks to combine various disciplines with religious knowledge, thus giving birth to strong and solid Islamic values. Meanwhile, this pesantren also has an educational path outside the pesantren which is provided through family education activities, routine teaching activities, special recitation for mothers, special courses for religious studies, routine tadarus and various studies of PERSIS scholars broadcast through PERSISTV. Thus the various activities presented through this educational model and system are able to produce students who have graduates who are competent in all fields. These graduates are proven by the presence of entrepreneurs, scientists, well-known figures, education practitioners, and scholars who were born thanks to the education that has been organized by the Islamic Boarding School 1-2 Bandung.